2019
DOI: 10.1111/jcmm.14355
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐SULT1C2A regulates Foxo4 in congenital scoliosis by targeting rno‐miR‐466c‐5p through PI3K‐ATK signalling

Abstract: Congenital scoliosis (CS) is the result of anomalous vertebrae development, but the pathogenesis of CS remains unclear. Long non‐coding RNAs (lncRNAs) have been implicated in embryo development, but their role in CS remains unknown. In this study, we investigated the role and mechanisms of a specific lncRNA, SULT1C2A, in somitogenesis in a rat model of vitamin A deficiency (VAD)‐induced CS. Bioinformatics analysis and quantitative real‐time PCR (qRT‐PCR) indicated that SULT1C2A expression was down‐regulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) are longer than 200 nucleotides in the length, usually up to approximately 100 kb. 1,[13][14][15][16] LncRNAs have showed to be deregulated in many tumors, such as hepatocellular carcinoma, lung cancer, nasopharyngeal carcinoma, breast cancer and gastric cancer. [17][18][19][20][21][22] More studies have suggested that lncRNAs play a functional role in several biological processes, such as cell development, proliferation, invasion, apotosism, stem cell pluripotency and differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs) are longer than 200 nucleotides in the length, usually up to approximately 100 kb. 1,[13][14][15][16] LncRNAs have showed to be deregulated in many tumors, such as hepatocellular carcinoma, lung cancer, nasopharyngeal carcinoma, breast cancer and gastric cancer. [17][18][19][20][21][22] More studies have suggested that lncRNAs play a functional role in several biological processes, such as cell development, proliferation, invasion, apotosism, stem cell pluripotency and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are longer than 200 nucleotides in the length, usually up to approximately 100 kb 1,13–16 . LncRNAs have showed to be deregulated in many tumors, such as hepatocellular carcinoma, lung cancer, nasopharyngeal carcinoma, breast cancer and gastric cancer 17–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Our team has shown that embryonic expression of the lncRNA SULT1C2A was decreased whereas miR-466c-5p was upregulated in the rat model of vitamin A deficiency-induced congenital scoliosis. 43 Somitogenesis-related genes, such as Foxo4, Sox9, Pax1 and Nkx3-2, were downregulated on gestational day 9 upon maternal vitamin A deficiency. In this regard, reduced expression of SULT1C2A was found F I G U R E 1 Pathogenic mechanism of deregulated ncRNAs in scoliosis to increase the availability of miR-466c-5p and thereby decreasing…”
Section: Sult1c2a and Mir-466c-5pmentioning
confidence: 99%
“…Our team has shown that embryonic expression of the lncRNA SULT1C2A was decreased whereas miR‐466c‐5p was upregulated in the rat model of vitamin A deficiency‐induced congenital scoliosis . Somitogenesis‐related genes, such as Foxo4, Sox9, Pax1 and Nkx3‐2, were downregulated on gestational day 9 upon maternal vitamin A deficiency.…”
Section: Functional Roles Of Key Ncrnas In Scoliosismentioning
confidence: 99%
“…Growing studies demonstrated that lncRNAs played roles in several cellular functions such as cell apoptosis, differentiation and proliferation [18][19][20][21][22]. LncRNAs were also deregulated in multiple diseases including tumors, coronary heart disease, scoliosis and intervertebral disc degeneration [23][24][25][26]. Recently, a new lncRNA HIX003209 has been identified and found to be invovled in the development of rheumatoid arthritis [27].…”
Section: Introductionmentioning
confidence: 99%